Integration of Learning Evaluation in the Islamic Curriculum: Pillars of Strengthening Contemporary Islamic Civilization - Aldi, Muhammad; Asrori, Mohammad; Khairanis, Retisfa; Zuhriyah, Indah Aminatuz (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study aims to analyze how the integration of learning evaluation in the Islamic curriculum can strengthen the foundation of Islamic civilization in the contemporary era. Evaluation in Islamic education focuses not only on academic aspects, but also on character building, moral values, and Islamic integrity. This research uses a qualitative approach with the method of literature study and field observation in several Islamic educational institutions that have implemented evaluation integration in their curriculum. The results show that systematically integrated evaluation in the Islamic curriculum is able to improve the quality of graduates who are not only intellectually intelligent, but also spiritually and socially strong. This evaluation encourages the creation of learning patterns that are more critical, applicable, and relevant to the demands of the times. The implication of this research is the need to develop an evaluation model based on Islamic values, in order to strengthen the competitiveness of Muslims in the global arena and revive a progressive, ethical and innovative Islamic civilization.